A REVIEW ON THE APPLICATION OF REMOTE SENSING AND GEOGRAPHIC INFORMATION SYSTEM IN FLOOD CRISIS MANAGEMENT - Abid, Sheikh Kamran; Sulaiman, Noralfishah; Mahmud, Nur Putri Najwa; Nazir, Umber; Adnan, Nur Azhani (Innovare Academics Sciences PVT. LTD, 2020)
Flood is considered as one of the most devastating hazards around the globe and emerged as an important issue among all the stakeholder to manage. Every year when the flood occurs, it has a terrible impact on human lives and demolishes billions of dollars property and infrastructure as well. The flood catastrophe and its losses can be reduced and prevented by flood inundation maps which provides a reliable and accurate information to the public. The principle objective of this paper is to review the application of Geographical information system (GIS) and technology of Remote sensing (RS) in geospatial skills and expertise in sciences, the integration and utilization of spatial and information technology effectively and more prominence is on using non-structure approaches based on remote sensing and geographic information system in flood crisis management. The advantages of solving complex logistics operations, accuracy with high speed which provides a reliable change, improved communication, monitoring capability, modeling, estimation of flood risk, promoted a cost saving mechanism with greater efficiency/friendly adaptability with the environment of theses digitize systems purposes to using more and more spatial application in flood crisis management. Geospatial information and remote sensing utilization serves as bridge between the flooding security measures and early prediction system. The paper encompasses the advantages of RS & GIS which acts as a tool in monitoring and improving before, during and after the flood crisis management in Malaysia.